ACCOUNTING FOR GUARANTEED WAGE PLANS. - Seiler, Robert E. (The Accounting Review, 1956)
This article focuses on accounting for guaranteed wage plans. Most of the wage leveling plans are basically employee withholding plans whereby some of the earnings of the employee are withheld and are paid to him later when his earnings are low. The obvious disadvantage of this plan lies in the employee's reluctance to having part of his earnings withheld. The majority of wage leveling plans have therefore created little employee enthusiasm, for they are little more than savings plans, supervised by the company. A major difference between the leveling and the minimum-guarantee type of plan is the number of employees that are covered. Where the wage process is primarily one of leveling wages, there is no excessive cost to the employer for time not worked. One of the most complex accounting problems arising out of recent developments in guaranteed wage payments is concerned with the special exemptions allowed for the payment of overtime premiums under the Fair Labor Standards Act. The record-keeping process is further complicated if the company is to take advantage of the overtime premium relief provisions of the Fair Labor Standards Act.